A Box–Behnken Design-Based Model for Predicting Power Performance in Microbial Fuel Cells Using Wastewater. Issue 1 (2nd January 2017) - Martínez-Conesa, E. J.; Ortiz-Martínez, V. M.; Salar-García, M. J.; De Los Ríos, A. P.; Hernández-Fernández, F. J.; Lozano, L. J.; Godínez, C.
Abstract : Although modeling is regarded as a useful tool to understand the performance of microbial fuel cells (MFCs), the number of MFC models remains very low compared with the number of experimental works available in the literature. Moreover, there are very few MFC modeling attempts dealing with the use of wastewater as fuel in these devices, which is essential for the practical implementation of MFCs since the potential of this technology lies in the two-fold benefit of wastewater treatment and bioenergy generation. In this work, a four-factor three-level Box–Behnken design was developed to model the electrochemical power generation in two-chamber MFCs using wastewater as fuel. The optimum values of temperature, external resistance, feed concentration and anodic pH that maximized power output were investigated. Optimum conditions were found at T = 35°C and R = 1 kΩ, corresponding to a maximum power density of 0.88 W·m −3, while feed concentration and pH did not show statistical significance in the ranges studied. Thus, a Box–Behnken design-based model as empirical approach could provide an effective tool for the optimization study of MFC systems.